Indonesian University Students’ Perceptions on the Use of Social Media for English Language Learning - Seli, Fenny Yutika (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
The use of social media is not only for communicating and enjoying leisure time but also for learning many things. Since that, English-related content has been one of the things that often be on their search. Various educative content can be found on social media. This study aims to find out the students’ perceptions on the use of social media for English language learning. The participants of this study are 98 university students in Jakarta. A descriptive qualitative method was used. The data was obtained by using a questionnaire and interview. The results showed that Instagram, YouTube, and TikTok are the most preferred platform for learning. The students have positive perceptions on the use of social media for English learning because social media is easy to access, fun, stress-free, and reinforces their independence. In addition, the most skill that can be learned from social media are reading.